Improved accuracy of geographical origin identification of shiitake grown in sawdust medium: A compound-specific isotope model-based pilot study. (1st February 2022) - Chung, Ill-Min; Kim, Yun-Ju; Moon, Hee-Sung; Han, Jae-Gu; Kong, Won-Sik; Yarnes, Christopher T.; Kim, Seung-Hyun
Highlights: The CSIA-model improved the authentication of the origin of shiitake. CSIA differentiates Chinese-inoculated medium shiitake from Chinese origin shiitake. Glutamate and aspartate δ 15 N were the most crucial markers of shiitake origin. The predictability of the classification for the cross-validated set was 96.4%. Abstract: In countries like South Korea and the USA, origin labeling of shiitake grown using imported Chinese-inoculated medium is an issue. Therefore, we evaluated the use of compound-specific isotope analysis (CSIA) for the accurate identification of the geographical origin of shiitake (Korean, Chinese-inoculated medium, and Chinese); Chinese-inoculated medium shiitake were cultivated in Korea using inoculated sawdust medium from China. The CSIA-discriminant model showed an overall accuracy of 100% in the geographical classification of the original set and 96.4% for the cross-validated set. Glutamate and aspartate δ 15 N values were the most important variables for differentiating shiitake based on their origins. Compared to that observed upon using the bulk stable isotope analysis, the CSIA model was associated with significantly improved predictability of origin identification. Our findings elucidate the importance of isotope signatures in developing a reliable origin labeling method for shiitake cultured on the sawdust medium for the global market.